2012
DOI: 10.5539/elt.v5n9p45
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Instruction Based on Multiple Intelligences Theory on the Attitude and Learning of General English

Abstract: The purpose of the present study is investigating the effect of instruction based on Multiple intelligence (MI) theory on attitude and learning of General English course among students of Islamic Azad University, Kermanshah Branch in the second semester of educational year of 2010-2011. 61 male and female students in two different classes participated in the present study that were assigned to experimental (32 students) and control (29students) groups based on random cluster sampling. A quasi experimental meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
4
9
0
Order By: Relevance
“…More specifically, in MI-based teaching, students were allowed to learn in the way they feel most comfortable with. This finding is in line with Soleimani et al (2012), Le Thi Tuyet Hanh and Tran Ba Tien (2017). In other words, to help students achieve educational aims and reduce their anxiety in solving learning problems, the activities should be interesting enough and give learners different options to approach the problems.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…More specifically, in MI-based teaching, students were allowed to learn in the way they feel most comfortable with. This finding is in line with Soleimani et al (2012), Le Thi Tuyet Hanh and Tran Ba Tien (2017). In other words, to help students achieve educational aims and reduce their anxiety in solving learning problems, the activities should be interesting enough and give learners different options to approach the problems.…”
Section: Discussionsupporting
confidence: 89%
“…This study aims to investigate if MI-related projects have any contributions in promoting EFL learner's autonomy. According to Soleimani et al (2012), "MI framework helps learners gain better self-awareness about learning abilities in different intelligence areas" (p. 50). It is hoped that the results will help gain more understanding of Vietnamese EFL learners' autonomy, thereby designing more effective projects to motivate students to be autonomously engaged in their English language learning.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, students who teach based on multiple intelligence theories exceed students who are traditionally instructed both in general and in each sub-English learning skills (vocabulary, reading comprehension, and structure). The results also showed that students' attitudes towards learning English in the experimental group increased significantly [7]. Thus using multiple intelligences has more impact than just using one or two intelligences.…”
Section: Literature Reviewmentioning
confidence: 83%
“…Referring to the field of language instruction, some studies have reported the positive effects of MI-based instruction on English language learning. Comparing traditional approaches and MIBI, MIBI affects students' attitudes positively toward English language learning (Jing, 2013;Soleimani et al, 2012). Besides, it is found that several English teaching strategies can accelerate the activation of different intelligences in individual students (Kartiah et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 98%